Alfred Tarski e o conceito de verdade em linguagens formalizadas - Lima, Leonardo Weber Castor de (2004)
In this work we offer a general presentation of Alfred Tarski’s semantical investigations. Particularly we focus on his contribution to the mathematical formalization of the concept of truth. Our presentation includes especially a study of the monograph The Concept of Truth in Formalized Languages, as well as a study of the Tarskian notion of criterion of truth – a relatively neglected notion in logico-philosophical literature.